2012
DOI: 10.1371/journal.pone.0043646
|View full text |Cite
|
Sign up to set email alerts
|

XB130 Mediates Cancer Cell Proliferation and Survival through Multiple Signaling Events Downstream of Akt

Abstract: XB130, a novel adaptor protein, mediates RET/PTC chromosome rearrangement-related thyroid cancer cell proliferation and survival through phosphatidyl-inositol-3-kinase (PI3K)/Akt pathway. Recently, XB130 was found in different cancer cells in the absence of RET/PTC. To determine whether RET/PTC is required of XB130-related cancer cell proliferation and survival, WRO thyroid cancer cells (with RET/PTC mutation) and A549 lung cancer cells (without RET/PTC) were treated with XB130 siRNA, and multiple Akt down-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 50 publications
5
53
0
1
Order By: Relevance
“…By acting as an upstream regulator of PI3K, XB130 plays an important role in mediating cell survival and proliferation through Akt pathways [21] and in cell migration through Rac-dependent pathways [12, 19]. The role of XB130 is not limited to protein activity and several studies have shown that XB130 also participates in the regulation of gene expression [14] (Figure 4).…”
Section: Cellular Functions Of Xb130mentioning
confidence: 99%
“…By acting as an upstream regulator of PI3K, XB130 plays an important role in mediating cell survival and proliferation through Akt pathways [21] and in cell migration through Rac-dependent pathways [12, 19]. The role of XB130 is not limited to protein activity and several studies have shown that XB130 also participates in the regulation of gene expression [14] (Figure 4).…”
Section: Cellular Functions Of Xb130mentioning
confidence: 99%
“…XB130 is a tyrosine kinase substrate, which can be tyrosine phosphorylated by Src and other tyrosine kinases [7][9], and interact with Src through its N-terminal SH2 and SH3 domain binding motifs, and mediates Src related transactivation of SRE and AP-1 [7]. The N-terminus of XB130 also contains a YxxM motif that can bind to the p85α subunit of phosphatidyl inositol 3-kinase (PI3K) through its SH2 domains, and subsequently activate Akt [2], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminus of XB130 also contains a YxxM motif that can bind to the p85α subunit of phosphatidyl inositol 3-kinase (PI3K) through its SH2 domains, and subsequently activate Akt [2], [8]. XB130 mediates cell survival and proliferation through multiple signals down-stream from Akt [9]. XB130 in human thyroid cancer cells regulates tumor growth as shown in an animal model with nude mice, through promotion of cell proliferation and inhibition of apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, XB130 was also identified in different cancer cells in the absence of RET/PTC, and subsequent to stimulating Akt, XB130 was found to regulate cancer cell cycle progression and survival through multiple Akt downstream molecules (67). For example, the cyclin-dependent kinase inhibitor p27Kip1 nuclear translocation can cause G1 arrest and the cyclin-dependent kinase inhibitor p21Cip1/WAF1 can negatively modulate cell cycle progression by inhibiting the activation of the cyclin/cdk2 complex.…”
Section: Mechanism Of Xb130 In Cancermentioning
confidence: 99%